Tribological performance analysis of nanocellulose-AL2O3-engine oil - Amirruddin, Abdul Kadir (2019)
In the current studies, the nano-lubricants have been the vital role in all machine components in preventing wear and tear due to relative motion between the contact surfaces such as bearings, camshaft, piston, gearbox, lead screw, metal working, fluids, gears, and in automotive air-conditioning. Given continuous environmental legislation, the lubrication industry has been striving to produce environmentally suitable lubrication alternatives for internal combustion engines. Addressing this challenge requires the use of lubricants that conforms to environmental standards while maintaining excellent lubrication performance. This thesis investigates the tribological viability of hybrid lubricants in improving the performance of the nano-lubricants, research is done by using Nano cellulose (CNC) and Aluminium Oxide (Al2O3) as the hybrid nano-lubricant, being as the promising alternative and solution for tribological behaviour of both solid and liquid lubrication and extends the life of the mechanical components which CNC is well known as a good heat conductor due to its structural arrangement that allow to conduct heat. The hybrid of nano-lubricant with different ratios as additives in engine oil is then used to conduct thermo-physical properties as to reduce the COF and WR of similar piston material. The nano-lubricant is prepared with multiple ratios 0.3 %, 0.5 % and 0.7 % concentration which were compared to base oil 10W-40 and tested for properties at 30 ºC, 50 ºC and 70 ºC. Thermal conductivity and dynamic viscosity showed a positive response to the comparison with base oil as for thermal conductivity, it increases as temperature increases while dynamic viscosity reduces as the temperature increases. Nano-hybrid lubricant has the highest thermal conductivity enhancement compared with 10W-40 base oil at 18.09 %. Meanwhile, nano-lubricant exhibit lowest enhancement of dynamic viscosity compared with 10W-40 base oil at 21.8 %. As per over all property test, 0.5 % nano-hybrid lubricant concentration has the best result. The visual observation displayed a very small sedimentation which is insignificant and samples are considered stable throughout the stability test done for two months. Optimisation finding that hybrid (CNC+Al2O3) nano-lubricant produced less friction, less wear effect and it can stand high load. Based on the research finding, it can be concluded that the research objectives are achieved. The hybrid Al2O3 nanoparticles + CNC can be used as additive in lubricant in reducing the COF (16 %) and WR (71 %). Moreover, this study has shown that the used of the Al2O3 nanoparticles have the potential to improvise the lubricant for better durability to apply in the system replicating an internal combustion engine of an actual car.